Interrelationship between Three Dimensions of Sustainable Performance Measurement among Malaysian Manufacturing Companies - TEH, Boon Heng; ABDUL RAHMAN, Abdul Aziz; ONG, Tze San; NG, Sin Huei; MAGSI, Hussain Bakhsh (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).07, 2022)
Corporate financial responsibility is the sole driving force of business in the business sector, as the primary goals of a firm are to maximize profit and grow shareholder value. However, in the previous decade, larger corporate obligations have been recognized, including environmental, local community, working conditions, and ethical standards. With the rise of "sustainability" reasons, unprecedented climate change is being measured into corporate strategy in the direction of sustainable thinking. The triple bottom line (TBL) is a sustainability assessment that combines environmental and social factors in addition to profitability and the rate of return on investment. The purpose of this research is to look into the interrelationships between the three dimensions of sustainable performance measurement (SPM) in Malaysian manufacturing companies. A questionnaire is issued to 600 manufacturing companies in the Federation of Malaysian Manufacturers (FMM) as part of a quantitative data collection approach. All the proposed hypotheses are supported, thus showing the interrelationship between three dimensions of SPM existed. Consequently, Malaysian companies are lagging behind in terms of SPM’s adoption compared to developed countries. Because of that, more government efforts to facilitate the adoption of SPM practice among companies are needed. The sole focus on the manufacturing industry, accuracy of data collection and time constraint are the limitations of this study. Therefore, it is suggested that further research should explore more the interrelationship between the three dimensions of SPM.